Crop diversity improves carbon, nitrogen and soil biological functions in an agroecological system - Ortíz, Jimena; Faggioli, Valeria; Zamora, Martín; Boccolini, Mónica; Lorenzón, Claudio; Gabbarini, Luciano Andrés (Asociación Argentina de la Ciencia del Suelo, 2023)
Agroecological management emerges as a promising alternative to current agricultural management, which is associated with impoverishment of environmental quality and soil fertility. Thus, the objective of this study was to evaluate the conversion from conventional to agroecological management by analyzing soil chemical and microbiological properties. This study was carried out in a field of the Barrow Experimental Farm of the National Institute of Agricultural Technology (INTA), Buenos Aires, Argentina, where two treatments were evaluated: agroecological (AE) and conventional management (CV). The soil sampling was carried out per soil-specific zones within each treatment. Samples were taken at 0 to 10 cm, and several soil chemical and microbiological parameters were determined. The AE management led to an evident restoration of soil fertility, since soil organic carbon, total nitrogen and pH showed increases of 21%, 16% and 3% respectively. The AE management also led to increases in the activities of enzymes involved in the carbon cycle (cellobiohydrolase and β-glucosidase), nitrogen cycle (N-acetyl-b-glucosamine) and sulfur cycle (arylsulfatase), and to an increase in the microbial biomass carbon, as well as in the diversity and richness of the bacterial community (p<0.05), probably due to the increase in the quality of the residues. These results are in agreement with previous studies, which have reported an increase in the diversity of bacteria when incorporating cover crops or leguminous intercrops. Bacterial and fungal communities differed between managements (PERMANOVA, bacteria p<0.017 r2=0.1074; fungi p<0.001, r2=0.1973). The bacterial and fungal communities of the AE management were the only ones that correlated positively and significantly with the soil properties measured, corroborating their key role in these systems. These results reaffirm the importance of improving aboveground and belowground biodiversity to maintain or restore soil fertility.
Keywords: Ciencias agrícolas::Agricultura, Silvicultura y Pesca::Ciencia del suelo